Crack Mapping on Shear-critical Reinforced Concrete Beams using an Open Source Digital Image Correlation Software - Benny Suryanto; Asdam Tambusay; Priyo Suprobo (Civil Engineering Dimension, 2017)
Three reinforced concrete beams, one with no shear reinforcement and two others with shear reinforcement ratios of 0.4% and 1.1%, were tested to investigate the influence of stirrup spacing on the mode of failure, overall strength and ductility. The results show that the beam reinforced with closely-spaced shear reinforcement failed in a ductile manner, whereas the other two beams with large stirrup spacing and no stirrup exhibited only a small measure of ductility and failed in a brittle manner. The importance of the provisions of maximum spacing is highlighted to ensure adequate anchorage for the stirrups and prevent a premature shear failure to occur. The application of a non-contact monitoring system employing the open source digital image correlation software Ncorr, an ordinary digital camera and a smartphone is demonstrated to provide a visualization of the cracking process throughout the load history.